2017
DOI: 10.1016/j.dib.2017.09.065
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reducing the incidence of gastrointestinal complications in patients treated with aspirin, referred to Imam Hospital, of Ahvaz, Iran

Abstract: This research contains data which were obtained during the analysis of treated patients with aspirin who were referred to Imam Hospital (Imam H) of Ahvaz, Iran; and the effect of this type of treatment (Helicobacter pylori eradicate (HPE)) on reducing the incidence of gastrointestinal complications. Studies have shown that taking aspirin in patients with Helicobacter pylori infection is associated with a decreasing risk of gastrointestinal bleeding (O'connor et al., 2013) [1]. In this study, 165 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Ahvaz Jundishapur University of medical sciences has six medical training centers, and in this study we selected three educational hospitals due to the volume of referrals and the fact that they have the most dialysis beds. Razi, Imam and Golestan educational hospital are a tertiary-care hospital with 220, 810 and 718 beds, located in Ahvaz ( 39 41 ) ( Figure 1 ). pH, SO 4 , Na, Ca, Mg, and HPC values were determined according to the standard methods ( 42 – 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ahvaz Jundishapur University of medical sciences has six medical training centers, and in this study we selected three educational hospitals due to the volume of referrals and the fact that they have the most dialysis beds. Razi, Imam and Golestan educational hospital are a tertiary-care hospital with 220, 810 and 718 beds, located in Ahvaz ( 39 41 ) ( Figure 1 ). pH, SO 4 , Na, Ca, Mg, and HPC values were determined according to the standard methods ( 42 – 45 ).…”
Section: Methodsmentioning
confidence: 99%
“…This cohort study was conducted during 2018 at Imam teaching hospital of Ahvaz (a tertiary-care hospital) with 900 beds approximately, in the southwest of Iran on 209 patients with chronic hepatitis B, who referred to the gastroenterology clinic of Imam Khomeini Hospital and the Gastroenterologist's Office in Ahvaz. 30 Ahvaz megacity Located in south west of Iran. It's the capital city of Khuzestan province, with an area of 140 square kilometers.…”
Section: Methodsmentioning
confidence: 99%
“…Ahvaz is a city with an area of 185 square kilometers that is the capital of Khuzestan Province (Southwest of Iran and Northern of Persian Gulf) in Iran and is located at 31°20′ N and 48°40′ E. [35][36][37][38][39][40][41][42] Razi, Golestan and Emam educational hospital are a tertiary-care hospital with 220, 425 and 600 beds, located in the south west of Ahvaz. [42][43][44] The location of the study area is shown in Fig. 1.…”
Section: Description Of Study Areamentioning
confidence: 99%